Occupational Contact Dermatitis in Employees of Large-Scale Narcotic Crop Farms of Ethiopia: Prevalence and Risk Factors. A Self-Reported Study Using the Nordic Occupational Skin Questionnaire - Aiggan Tamene (SAGE Publishing, 2021)
Background: Occupational skin diseases are the second leading occupational disease, accounting for almost 25% of all missed workdays. Occupational contact dermatitis (OCD) accounts for 70% to 90% of all skin disorders in the workplace. Only a few occupational epidemiology studies have looked into the prevalence and risk factors of occupation-induced dermatitis among narcotic crop farm workers around the world. Related studies in Ethiopia are even fewer. Methods: A cross-sectional survey was conducted in the Dirashe district of Southern Ethiopia from March 23 to April 12, 2021. Data was collected using a standardized interviewer-administered questionnaire. The history of contact dermatitis was determined using the standardized Nordic Occupational Skin Questionnaire version 2002 (NOSQ-2002). A total of 578 farm laborers took part in the study, which was conducted using a systematic random sampling. Descriptive statistics and multivariable regression were used to characterize the data and identify factors associated with occupational contact dermatitis. Result: The prevalence of self-reported occupational contact dermatitis in the past 12 months among workers of large-scale Khat farms was (AOR: 67.80%, 95% CI [61.00, 76.23]). In the multivariable regression, being older (AOR: 5.51, 95% CI [1.79, 7.24]), working as a bundle binder (AOR: 5.74, 95% CI [2.12, 15.55]), not wearing personal protective equipment (PPE) (AOR: 2.50, 95% CI [1.64, 3.81]), and having poor knowledge of pesticides use, storage, and disposal methods (AOR: 2.50, 95% CI [1.64, 3.81]) were associated with occupational contact dermatitis. Conclusion: Contact dermatitis caused by work is very common among Khat farm laborers. Measures to promote safe practices and reduce exposure to hazards, such as removing expired and/or banned chemicals, purchasing alternative pesticides that meet legislative requirements, job rotation and routine training of staff on safe practices, increasing safety signage, and performing risk assessments, as well as improving the quantity and quality of institutional protective equipment supplies may thus contribute to the enhancement of safe work practices.